1993
DOI: 10.1172/jci116374
|View full text |Cite
|
Sign up to set email alerts
|

Processing of epidermal glucosylceramides is required for optimal mammalian cutaneous permeability barrier function.

Abstract: The interstices of the mammalian stratum corneum contain lipids in a system of continuous membrane bilayers critical for the epidermal permeability barrier. During the transition from inner to outer stratum corneum, the content of polar lipids, including glucosylceramides, decreases while ceramide content increases. We investigated whether inhibition of glucosylceramide hydrolysis would alter epidermal permeability barrier function. Daily topical applications of bromoconduritol B epoxide (BrCBE) to intact muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
201
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(209 citation statements)
references
References 46 publications
8
201
0
Order By: Relevance
“…Previous studies demonstrate that initial lipid processing normally occurs in extracellular domains (3), and that it is this initial lipid processing step, at the SG-SC interface and in the lower SC, that is disturbed in: 1) neutral buffer-exposed skin, 2) NHE1 Ϫ/Ϫ mice, and 3) normal mice treated with the specific NHE1 inhibitor, HOE694. This view is supported by insights from other knockout models/ diseases, which also reveal the SG-SC interface to be an area of intense enzymatic lipid processing activity (5)(6)(7)32). Here we show with FLIM that this compartment is already acidified in normal skin, contrary to the conventional view of the pH gradient obtained with flat electrodes, which would predict this compartment to be neutral.…”
Section: Nhe1 Regulates Epidermal Ph and Barrier Functionmentioning
confidence: 81%
“…Previous studies demonstrate that initial lipid processing normally occurs in extracellular domains (3), and that it is this initial lipid processing step, at the SG-SC interface and in the lower SC, that is disturbed in: 1) neutral buffer-exposed skin, 2) NHE1 Ϫ/Ϫ mice, and 3) normal mice treated with the specific NHE1 inhibitor, HOE694. This view is supported by insights from other knockout models/ diseases, which also reveal the SG-SC interface to be an area of intense enzymatic lipid processing activity (5)(6)(7)32). Here we show with FLIM that this compartment is already acidified in normal skin, contrary to the conventional view of the pH gradient obtained with flat electrodes, which would predict this compartment to be neutral.…”
Section: Nhe1 Regulates Epidermal Ph and Barrier Functionmentioning
confidence: 81%
“…Moreover, given the large hydrophobic binding pockets in CD1d, the presence of CD1d on the outer layers of epidermis in psoriatic plaques opens up the possibility that various glycolipids present in the stratum corneum could play a role in triggering a response by NK-T cells or other T cell subsets capable of recognizing such glycolipids in the context of CD1d. During epidermal differentiation keratinocytes produce different amounts and types of various glycolipids, including glucosylceramides (49). Alterations in these glycolipids in the stratum corneum can have a significant impact on the barrier function of skin.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we found that loss of ABCA12 activity did not significantly affect skin-free fatty acids levels, including that of linoleic acid, which indicates that the loss of the linoleic ceramide esters was not secondary to insufficient cellular linoleate supplies. Although it is formally possible that ABCA12 could play a role in transporting ␤-glucocerebrosidase rather than its substrate lipids, studies in animals either lacking the enzyme in the skin or treated with an enzyme inhibitor have reported no disruption of the epidermal lamellar body structure (38,39). Additionally, loss of ␤-glucocerebrosidase, or its activator Saposin-C caused a different spectrum of ceramide and glucosylceramide alterations in the skin than those we report here in the Abca12 Ϫ/Ϫ mice (40,41).…”
Section: That Their Abca12mentioning
confidence: 99%